Letters to Alice : birth of the Kleberg-King Ranch dynasty - Kleberg, Robert Justus, 1853-1932 (Gulf Coast books, 2012)
"In the summer of 1881, Robert Justus Kleberg rode across the hot, dusty South Texas brush country to the palatial home of Capt. Richard King to consult with the cattle baron about attending to his legal affairs. On that same journey, the young lawyer also first laid eyes on Alice King, "Princess of the Wild Horse Desert." Neither of their lives would ever be the same. Published for the first time in this book, the love letters written by Kleberg to Alice Gertrudis King provide a glimpse of the lives of two of the most influential people in Texas history. Editors Jane Clements Monday and Frances Brannen Vick have also provided generous documentation and annotation of these important primary documents from the Special Collections at Texas A & M University-Corpus Christi, affording historians and interested readers an insider's view of one of the world's greatest ranching empires as it transitioned from its founders to the next generation. Letters to Alice: Birth of the Kleberg-King-Ranch Dynasty represents the only existing collection of letters between any of the great Texas cattle barons and their wives. Although a great deal is already known about the ranch and its development, Monday and Vick present for the first time Robert Justus Kleberg's personal perspective on his first meeting with Alice King, their early courtship, the difficulties obtaining her parents' permission to marry, and the poignant time surrounding Captain King's death."--Provided by publisher.